Organic fertilization on the productivity of biofortified sweet potato - Reis, Clene Santos; Parra-Serrano, Luisa Julieth; Silva, Karolline Rosa Cutrim; Costa, Romário Martins; Aguiar, Francisco Ivo dos Santos (Scientia Agraria Paranaensis, 2022)
Sweet potato (Ipomoea batatas (L.) Lam.) is a widely grown vegetable in Brazil. The application of organic fertilizers of animal origin is considered a useful and economical practice for producers because it enhances soil fertility and ensures conservation. The objective of this study was to evaluate the commercial potential and total productivity of biofortified sweet potato based on the concentration of applied tanned bovine manure. This study was conducted from February to July 2020 in the experimental area of the Center for Agricultural and Environmental Sciences, Federal University of Maranhão (UFMA), Brazil. The experimental design used was randomized blocks with six treatments (0, 10, 20, 30, 40., and 50 Mg ha-1 of tanned bovine manure) and five replicates. The following agronomic characteristics of sweet potatoes were evaluated: fresh and dry biomass of the shoot (Mg ha-1), fresh and dry biomass of the tuberous root (Mg ha-1), number of commercial roots, and damage galleries (and holes) caused by insects. Bovine manure can be used as a source of organic fertilizer in the range of 10.0-20.0 Mg ha-1 to improve the productivity of biofortified sweet potato ‘Beauregard’. The yield was 7 Mg ha-1 with 10 Mg ha-1 of bovine manure, and this yield is higher than the average yield for the state of Maranhão.